A high‐resolution X‐ray fluorescence spectrometer and its application at SSRF. (10th September 2013) - Gao, Xing; Gu, Songqi; Gao, Qian; Zou, Yang; Jiang, Zheng; Zhang, Shuo; Wei, Xiangjun; Yu, Haisheng; Sheng, Guodong; Duan, Peiquan; Huang, Yuying
<x xml:space="preserve">Abstract</x> A high‐resolution X‐ray fluorescence spectrometer based on Rowland circle geometry was developed and installed at BL14W1 XAFS beamline of Shanghai Synchrotron Radiation Facility. The spectrometer mainly consists of three parts: a sample holder, a spherically curved Si crystal, and an avalanche photodiode detector. The simplicity of the spectrometer makes it easily assembled on the general purpose X‐ray absorption beamline. X‐ray emission spectroscopy and high‐resolution X‐ray absorption near edge spectroscopy can be carried out by using this spectrometer. X‐ray emission preliminary results with high‐resolution about 3 eV of Mn compounds were obtained, which confirmed the feasibility of the spectrometer. The application about Eu (III) retention on manganese dioxide was also studied using this spectrometer. Compared with conventional X‐ray absorption fine structure spectroscopy technique, the fluorescence peak of probed element [Eu (III) Lα] and matrix constituents (Mn Kα) were discriminated using this technique, indicating its superiority in fluorescence detection. Copyright © 2013 John Wiley & Sons, Ltd.